2017
DOI: 10.1007/s40519-017-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Personality, emotion-related variables, and media pressure predict eating disorders via disordered eating in Lebanese university students

Abstract: Findings from this study provide an understanding of the dynamics between DE, ED, and key personality, emotion-related, and social factors in youth. Lastly, implications and recommendations for future studies are advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 75 publications
2
17
1
2
Order By: Relevance
“…Appraisal of one’s own emotions, emotional regulation and optimism were found to be significantly lower in all measures of disordered eating, with emotional utilisation significantly lower in relation to attitudes and behaviour scores, suggesting that these elements of EI may be more important in understanding eating disorder aetiology. This is supported by previous research within the field which has suggested that eating disorders occur as a result of emotional dysfunction and regulation difficulties [ 6 8 , 13 , 25 ]. This suggests that disordered eating behaviours may occur due to an individual’s inability to regulate their emotions in response to stressors or triggering events.…”
Section: Discussionsupporting
confidence: 81%
“…Appraisal of one’s own emotions, emotional regulation and optimism were found to be significantly lower in all measures of disordered eating, with emotional utilisation significantly lower in relation to attitudes and behaviour scores, suggesting that these elements of EI may be more important in understanding eating disorder aetiology. This is supported by previous research within the field which has suggested that eating disorders occur as a result of emotional dysfunction and regulation difficulties [ 6 8 , 13 , 25 ]. This suggests that disordered eating behaviours may occur due to an individual’s inability to regulate their emotions in response to stressors or triggering events.…”
Section: Discussionsupporting
confidence: 81%
“…Research also needs to investigate PD comorbidity as well as the stability and predictive value of personality among people with DSM-5 [1] atypical AN, BN and BED of low frequency and/or limited duration, and purging disorder. In addition, research linking personality and EWDs amongst men and people with different ethnicity/race is needed [33,54,55], since the majority of extant studies in this area have focused on female Caucasian samples [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that social factors (e.g., media pressure) and specific personality traits (e.g., perfectionism) interact to predict disordered eating behaviours [33]. Another study showed that professional models are at a higher risk of developing negative automatic thoughts and dysfunctional assumptions relating to body weight, size, and shape if they endorse high scores on specific personality (e.g., narcissistic) styles [34].…”
Section: Multi-factor Nature Of Eating and Weight Disorder And Personmentioning
confidence: 99%
“…A razón de lo anteriormente señalado, se refleja la complejidad y necesidad de tener una delimitación más clara del constructo de alimentación emocional, así como su evaluación y creación de modelos explicativos, que permitan una mayor comprensión de la AE, así como una distinción más clara frente a constructos como la desinhibición/atracón. Por lo que la investigación, en este sentido, tiene un amplio campo de estudio para favorecer la implementación de intervenciones que contribuyan a decrementar la prevalencia de patologías como el sobrepeso y la obesidad, el síndrome metabólico, los TAIA, etcétera [12][13][14][15][16][17][18].…”
Section: Conclusionesunclassified
“…En este sentido, a las personas que tienen una mayor inclinación por la utilización de este tipo de ingesta se les ha denominado como "comedores emocionales", con la particularidad de tener una mayor susceptibilidad al distrés, así como mayor sensibilidad neurofisiológica al refuerzo [10,11]. Por otra parte, respecto a los efectos de la AE en la salud física y psicológica (principalmente en los comedores emocionales negativos), las primeras investigaciones apuntaban en exclusividad hacia un impacto en el peso corporal, como es en la obesidad, posteriormente a razón de su relación con la conducta alimentaria desinhibida, se comenzó a estudiar la relación de la AE con los nombrados actualmente trastornos alimentarios y de la ingesta de alimentos (TAIA), identificando principalmente que este patrón alimentario puede fungir como un factor precipitante del trastorno por atracón (TPA); por otra parte, en pacientes que han sido sometidos a cirugía bariátrica se ha reportado que la AE implica mayor interferencia en la pérdida de peso; cabe señalar que, este tipo de ingesta también se ha encontrado asociada con el síndrome metabólico [4,[12][13][14][15][16][17][18]. El impacto de la AE en la salud física y psicológica en población adulta, cobra relevancia al revisar las estadísticas mundiales, principalmente en cuanto al sobrepeso y la obesidad, así como en los TAIA.…”
Section: Introductionunclassified